2019
DOI: 10.1016/j.psyneuen.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic-inflammatory status as predictor of clinical outcome at 1-year follow-up in patients with first episode psychosis

Abstract: In this sample of FEP patients, inflammation and metabolism, closely correlated at the onset of psychosis, proved to play a key role as predictors of the clinical course of psychosis when combined in a single factor. These findings offer an important potential target for early screening and interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 46 publications
4
23
0
Order By: Relevance
“…A multitude of studies and meta-analyses show that patients with major depressive disorder (MDD) have, on average, increased serum levels of pro-inflammatory cytokines, like interleukin 1 beta (IL-1-beta), IL-6 and tumour necrosis factor alpha (TNF-alpha), and of the acute phase protein, C-reactive protein (CRP) 1,2,4,5 . Patients with 'treatment resistant depression' (TRD) are more likely to have increased inflammation 6,7 , as do patients with cardiovascular disorders, obesity, anxiety, and a history of childhood maltreatment 3,[8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…A multitude of studies and meta-analyses show that patients with major depressive disorder (MDD) have, on average, increased serum levels of pro-inflammatory cytokines, like interleukin 1 beta (IL-1-beta), IL-6 and tumour necrosis factor alpha (TNF-alpha), and of the acute phase protein, C-reactive protein (CRP) 1,2,4,5 . Patients with 'treatment resistant depression' (TRD) are more likely to have increased inflammation 6,7 , as do patients with cardiovascular disorders, obesity, anxiety, and a history of childhood maltreatment 3,[8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Testing CRP levels in overweight patients with depression could be useful for recommending adjunct anti-inflammatory treatments or predicting their likelihood of developing additional comorbidities in the future. Indeed, several clinical trials have observed that higher BMI at baseline predicted a poorer response to antidepressant treatments (Jha et al, 2018;Uher et al, 2009), while we have previously shown that immune-metabolic status was associated with a poorer response to antipsychotic medication in individuals with psychosis (Nettis et al, 2019). Antiinflammatory drugs improve the therapeutic action of antidepressants (Bai et al, 2020;Haroon, Raison, & Miller, 2012), which could be particularly useful in the context of chronically inflamed overweight patients with depression.…”
Section: Discussionmentioning
confidence: 83%
“…A multinational, multi-center, randomized, double-blind study of first-episode psychosis patients showed that those with the most severe symptoms before treatment presented with higher pro-inflammatory compounds and were the most at risk of non-remission compared to psychosis patients with less severe symptoms (Martinuzzi et al, 2019). Additionally, in a longitudinal study of first-episode psychosis patients an association was found between increased high-sensitivity CRP, triglycerides and BMI at baseline, and higher PANSS scores and reduced treatment response at 1-year follow-up (Nettis et al, 2019).…”
Section: Discussionmentioning
confidence: 99%